2014
DOI: 10.1093/toxsci/kfu187
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Diesel Emissions Generated with Cerium Oxide Nanoparticle Fuel Additive Induce Adverse Pulmonary and Systemic Effects

Abstract: Diesel exhaust (DE) exposure induces adverse cardiopulmonary effects. Cerium oxide nanoparticles added to diesel fuel (DECe) increases fuel burning efficiency but leads to altered emission characteristics and potentially altered health effects. Here, we evaluated whether DECe results in greater adverse pulmonary effects compared with DE. Male Sprague Dawley rats were exposed to filtered air, DE, or DECe for 5 h/day for 2 days. N-acetyl glucosaminidase activity was increased in bronchial alveolar lavage fluid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 64 publications
(82 reference statements)
1
40
1
Order By: Relevance
“…[46][47][48] It has been shown that a 4-week inhalation exposure to DECe in rats induced an increase of tissue factor, but not in PAI-1 concentration. 19 The discrepancy between the latter study showing the absence of an increase of PAI-1 …”
mentioning
confidence: 84%
See 3 more Smart Citations
“…[46][47][48] It has been shown that a 4-week inhalation exposure to DECe in rats induced an increase of tissue factor, but not in PAI-1 concentration. 19 The discrepancy between the latter study showing the absence of an increase of PAI-1 …”
mentioning
confidence: 84%
“…16,17 It is well-established that particulate air pollution and some engineered NPs affect the cardiovascular system either through inflammatory mediators produced in the lungs and released into the circulation or via their ability to cross the alveolar-capillary barrier and reach the cardiovascular system. 5,18 Since CeO 2 NPs have been shown to cross the alveolar-capillary barrier to reach extrapulmonary sites 19,20 and cause lung inflammation, 14,15,20 the present study hypothesized that these NPs can plausibly interact with the circulating platelets and vasculature and induce thrombotic events. This has not been investigated before, and, consequently, the aim of this study was to assess the acute (24 hours) effect of CeO 2 NPs on pulmonary and systemic inflammation and oxidative stress in mice and to evaluate their effects on coagulation in vivo and in vitro.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The third and most widespread source of REE-related air and soil pollution may refer to the global use of nCeO 2 as catalytic additives in diesel fuel. The limited number of publications in the literature thus far points to nCeO 2 as components of diesel exhaust particulate matter (Cassee et al 2011;2012;Ma et al 2014;Snow et al 2014), thus prompting investigations on the relevance and possible health implications of diesel exhaust particulate matter following human exposure to these elements at work or in the environment. Stunted animal growth and decreased chlorophyll production are among the forms of damage to animals and plants, respectively, that have been reviewed in separate chapters (4, 6, and 7; by Philippe J. Thomas, Giovanni Pagano, and Rahime Oral).…”
Section: Environmental and Occupational Issues Of Reesmentioning
confidence: 99%